Mapping the Scholarly Content on Information Literacy through Bibliometric and Altmetric Lenses - Lone, Abdul Wahid; Ayoub, Arshia (Information Research Communications, 2024)
Purpose The exponential growth in information as well as in its means and sources featured Information Literacy (IL) as vital skill in current period. Thus, purpose of the current study is to examine the literature published on IL and also analyze the correlation between altmetrics and the citation count of these published articles. Design/Methodology/Approach The study employed the Web of Science (WoS) database as the source for literature published on IL and used the required bibliometric measures to analyze the specific aspects of publishing trends. This study uses various bibliometric indicators to provide some insightful findings about the most productive authors, countries, and articles (using software SPSS and R). In addition, VOSviewer tools were used to create a graphical representation of the bibliometric data. Findings The findings reveal that the study covered articles from 1989-2022, i.e., a period of 33 years, and the most productive year was 2016. Further, the USA is the highest contributing country, and most articles published are multi-authored. The average number of citations received per document is 19.19. IL is the most frequent keyword with highest link strength with library instruction. A low positive correlation was observed between citation count and altmetric score. Originality The outcomes obtained will help researchers to encompass the literature published on IL, assess the trends, nature and types of research patterns being published. This analysis also reflects about the knowledge evolution of IL research domains and future trends.
Keywords: Information literacy; Meta-literacy; Digital literacy; Bibliometrics; Altmetrics